(untitled) (CIPEEX, 2024)
THIS IS AN ONGOING RESEARCH PROJECT RELATED TO A BROADER INITIATIVE AIMED AT ANALYZING, BASED ON THE THEORETICAL-METHODOLOGICAL ASSUMPTIONS OF ENVIRONMENTAL HISTORY, THE EXPANSION OF THE AGRICULTURAL FRONTIER IN THE CERRADO. OUR REFERENCES INCLUDE THE INTERPLAY BETWEEN HISTORY, ECOLOGY, AND DEVELOPMENT SCIENCE FOR AGRICULTURE. WE ARE INTERESTED IN EXAMINING GOVERNMENTAL, INSTITUTIONAL, AND ACTOR DISCOURSES AND PRACTICES INVOLVED IN THE AGRARIAN "CONQUEST" OF THE PHYTOPHYSIOGNOMIC SOILS OF BRAZILIAN FIELDS. OUR FOCUS IS ON THE CLOSED FIELDS OF CENTRAL BRAZIL, EMPHASIZING THE INCORPORATION OF THIS REGION INTO NATIONAL DEVELOPMENT POLICIES. WE ALSO SEEK TO IDENTIFY AND ANALYZE THE RELATIONSHIP BETWEEN THE AGRONOMIC DEVELOPMENT OF THE CERRADO AND THE MOST RECENT HISTORICAL PROCESSES OF ENVIRONMENTAL DEVASTATION IN THE BIOME. OUR TEMPORAL FRAMEWORK PRIMARILY COVERS THE CONTEXT OF DEVELOPMENTAL POLICIES IN BRAZIL, WITH A FOCUS ON DOCUMENTARY SOURCES PRODUCED BETWEEN THE 1950S AND 1990S. THIS INCLUDES DEBATES ON THE ECOLOGY OF SOILS AND SAVANNAH FIELDS IN CENTRAL BRAZIL. WE UTILIZE THE THEORETICAL ASSUMPTIONS OF ENVIRONMENTAL HISTORY TO UNDERSTAND THE "INVENTION" OR HISTORICAL CONSTRUCTION OF THE CERRADO AMID ECOLOGICAL IDEAS AND THE SYMBOLIC STRUGGLE BETWEEN DIFFERENT CONCEPTS. THIS CULMINATED IN THE HEGEMONIC VISION OF THE BIOME WITH THE GREAT AGRICULTURAL FRONTIER FROM BRAZIL. IN THIS CONTEXT, INTERDISCIPLINARY DIALOGUE WITH OTHER FIELDS OF KNOWLEDGE IS FUNDAMENTAL TO UNDERSTANDING THE ECOLOGICAL, POLITICAL, AND ECONOMIC REASONS THAT ENCOMPASS THE RELATIONSHIP BETWEEN SOCIETY AND THE NATURAL RESOURCES OF THE CERRADO. ECOLOGY, AGRONOMY, GEOGRAPHY, ARCHEOLOGY, GEOLOGY, SOIL BIOLOGY, AND OTHER AREAS OF KNOWLEDGE, ALONG WITH HISTORICAL FIELDS SUCH AS THE HISTORY OF SCIENCE, HISTORY OF AGRICULTURE, AND ENVIRONMENTAL HISTORY, FORM PART OF THIS INTERDISCIPLINARY APPROACH. THUS, OUR RESEARCH UNIVERSE SEEKS TO EXPAND THE HISTORIOGRAPHICAL SCOPE THROUGH THE LENSES OF INTERDISCIPLINARITY, CRITICAL TO THE THEORETICAL-METHODOLOGICAL ASSUMPTIONS OF ENVIRONMENTAL HISTORY. OUR INTENTION IS TO ESTABLISH AN ENVIRONMENTAL HISTORY OF THE CERRADO BASED ON THE HISTORICAL PROCESSES OF AGRICULTURAL EXPANSION IN THIS REGION, CURRENTLY THE MAIN PRODUCER OF AGRICULTURAL COMMODITIES IN THE COUNTRY, AND TO EXPLORE ITS ECONOMIC AND SOCIO-ENVIRONMENTAL EFFECTS. IN THE CASE OF THE WORK PLAN FOR THE SCIENTIFIC INITIATION SCHOLARSHIP, WE AIM TO TRAIN STUDENT RESEARCHERS IN HANDLING HISTORICAL DOCUMENTARY SOURCES, ARCHIVES, AND COLLECTING AND ANALYZING THESE SOURCES, ALL WITHIN THE FRAMEWORK OF THE THEORETICAL-METHODOLOGICAL ASSUMPTIONS OF ENVIRONMENTAL HISTORY.